EFFECTIVE COMPLAINT LETTER FOR ACADEMIC AND BUSINESS CONTEXT - Angel Aurora Butar Butar, Desi Ratna Sari, Afdaleni, (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2022)
Customer complaints — they come in the form of an abusive email, a scathing online review, an awkward face-to-face meeting, or an unexpected phone call. It's hard to hear, but the customer complaints that result from you, your products, your staff, or your services fall short of expectations. Although difficult and inconvenient, handling customer complaints is an important part of doing business, and they must be handled properly.